2016
DOI: 10.1093/heapol/czw060
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptations to a global health initiative: penalties for home births in Zambia

Abstract: Global health initiatives (GHIs) are implemented across a variety of geographies and cultures. Those targeting maternal health often prioritise increasing facility delivery rates. Pressure on local implementers to meet GHI goals may lead to unintended programme features that could negatively impact women. This study investigates penalties for home births imposed by traditional leaders on women during the implementation of Saving Mothers, Giving Life (SMGL) in Zambia. Forty focus group discussions (FGDs) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…5,6,30,38 † Both home-birth fines and userfees place the burden on poor women and increase health system inequity, as confirmed by a longstanding and growing body of evidence on the negative implications of user-fees, 8,9 and the recent studies on home-birth fines. 40 We showed that different actors are frustrated about userfees and their impact on the poor, especially because in Malawi non-institutional deliveries have become strongly associated with maternal deaths. 6 Our analysis highlights issues of intersectionality, with different social locations, power relations and experiences converging to shape inequity.…”
Section: Resultsmentioning
confidence: 86%
“…5,6,30,38 † Both home-birth fines and userfees place the burden on poor women and increase health system inequity, as confirmed by a longstanding and growing body of evidence on the negative implications of user-fees, 8,9 and the recent studies on home-birth fines. 40 We showed that different actors are frustrated about userfees and their impact on the poor, especially because in Malawi non-institutional deliveries have become strongly associated with maternal deaths. 6 Our analysis highlights issues of intersectionality, with different social locations, power relations and experiences converging to shape inequity.…”
Section: Resultsmentioning
confidence: 86%
“…Only when we analyse power relations from the global to the local level, and how these dynamically interact with policies, can we understand how inequities are shaped. Following other scholars, 7,11,36,43,44 we make a couple of suggestions towards more equitable health systems. First, utilising ethnography can generate a better understanding of the complex interactions between policy and dynamic power relations.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced trust in health workers and the government might have broader consequences of trust in public services and society more generally. 43 Our analysis has shown the need for considering aspects of power, health systems functioning and financing at the global, national and local level 44 to understand how health policies are implemented and what the consequences may be. We have shown how actors' priorities play a role in the "falling apart" of services, starting with the discontinuation of donor funding and the (de)prioritisation of Safe Motherhood at the national level.…”
Section: Resultsmentioning
confidence: 99%
“…The successful reduction of the maternal mortality ratio in Malawi, from 957 deaths per 100,000 live births in 1990 to 634 deaths per 100,000 live births in 2015, is often attributed to the community involvement approach and in particular, the fine system used by local chiefs [ 11 ]. The application of fines for home births is not unique to Malawi; it is reported in Zambia [ 12 ], Burkina Faso [ 13 ] and Tanzania [ 14 ], among others. In an evaluation of strategies to increase health facility deliveries, Butrick et al [ 11 ] suggest that a fine-based system is generally considered appropriate because it is more affordable for a developing country like Malawi, than an incentive system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is assumed that, because fining within the chiefs system in Malawi is embedded in traditional ways of regulating social behaviours, fines for women in the field of maternal health are socially acceptable. Health system actors may also justify penalties as a fair response to home delivery as communities have been educated about the importance of facility delivery [ 12 ]. Some authors, however, raise critical questions about the use of penalties as incentives to influence health-seeking behaviour.…”
Section: Introductionmentioning
confidence: 99%